Drug Reaction Syndrome with Eosinophilia and Systemic Symptoms. Case Presentation - Omar Rangel Betarte; Mileny Acosta Fonseca; Vanessa Flores Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Drug reaction syndrome with eosinophilia and systemic symptoms is a reaction of hypersensitivity which triggers due to multiple drugs such as antibiotics, anti-inflammatory, anti-convulsants which occur in 2,2 % of admitted patients. Its importance is related in the high mortality that can achieve 30 %. A case of a 5 year old boy with antecedents of diagnosed epilepsy, treated with carbamazepine, who short time after starting the treatment had fever for 11 days. Posteriorly cutaneous erythematous pruritic maculopapular skin lesions appeared. He was admitted with the diagnosis of prolonged febrile syndrome. Laboratory test showed eosinophilia, elevation of liver tests and C-reactive protein. A syndrome of drug sensitivity was considered induced by carbamazepine, after the result of skin biopsy anti-comicial is suspended thus improving the condition, with normalization of eosinophils and liver function. The patient progressed without fever and good general condition. The case is presented due to the low prevalence of this syndrome in the University Pediatric Hospital Paquito González Cueto. Cienfuegos.